Chamilo LMS Research Trend: A Systematic Literature Review - Nasrum, Akbar; Nasir, Agus (IJBLE Scientific Publications Community Inc., 2023)
Chamilo is an open-source Learning Management System that is rarely known by campus communities in Indonesia, even though this LMS has been published for quite some time. Very little research is related to Chamilo compared to other LMS such as Moodle. This study will examine research trends over the past ten years using the Systematic Literature Review method. The subjects studied were taken from the Dimension and Scopus databases. The tools used are VoS Viewer and Mendeley software. The unit of analysis used is the